More spaghetti, I say - Gelman, Rita Golden (New York : Scholastic, 1992)
Minnie the monkey is too busy eating spaghetti all day, in all ways-to play with Freddy.
TR/PS
Keywords: Stories in rhyme; Monkeys -- Fiction